Do longer root hairs improve phosphorus uptake? Testing the hypothesis with transgenic Brachypodium distachyon lines overexpressing endogenous RSL genes. Issue 4 (17th January 2018) - Zhang, Chunyan; Simpson, Richard J.; Kim, Chul Min; Warthmann, Norman; Delhaize, Emmanuel; Dolan, Liam; Byrne, Mary E.; Wu, Yu; Ryan, Peter R.
Summary: Mutants without root hairs show reduced inorganic orthophosphate (Pi) uptake and compromised growth on soils when Pi availability is restricted. What is less clear is whether root hairs that are longer than wild‐type provide an additional benefit to phosphorus (P) nutrition. This was tested using transgenic Brachypodium lines with longer root hairs. The lines were transformed with the endogenous BdRSL2 and BdRSL3 genes using either a constitutive promoter or a root hair‐specific promoter. Plants were grown for 32 d in soil amended with various Pi concentrations. Plant biomass and P uptake were measured and genotypes were compared on the basis of critical Pi values and P uptake per unit root length. Ectopic expression of RSL2 and RSL3 increased root hair length three‐fold but decreased plant biomass. Constitutive expression of BdRSL2, but not expression of BdRSL3, consistently improved P nutrition as measured by lowering the critical Pi values and increasing Pi uptake per unit root length. Increasing root hair length through breeding or biotechnology can improve P uptake efficiency if the pleotropic effects on plant biomass are avoided. Long root hairs, alone, appear to be insufficient to improve Pi uptake and need to be combined with other traits to benefit P nutrition.